2001
DOI: 10.1029/2000jd900622
|View full text |Cite
|
Sign up to set email alerts
|

A case study of orographic rainfall processes incorporating multiscaling characterization techniques

Abstract: Abstract. The Southern Alps field experiment was designed to identify the dominant rainfall processes in intense orographic events in the South Island of New Zealand and included the deployment of a rain gauge network and meteorological radar. Multiscaling statistics, used to characterize the rainfall from a single extreme event, revealed both orographic and temporal changes in the rainfall nature, with significantly more incessant rainfall observed in the higher-altitude regions. Central to this work was phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(84 citation statements)
references
References 20 publications
9
72
3
Order By: Relevance
“…In particular, for orographic precipitation see also e.g. Harris et al (1996), Purdy et al (2001), Nykanen and Harris (2003) and Deidda et al (2006). Two main reasons were identified by Deidda et al (2006) as contributing to different outcomes in rainfall analyses: a physical factor lies in the different orographic range covered by the data (a limited range may not represent a significant obstacle for perturbations); a second explanation may be the differences in the length of the observation periods (relatively brief observation period may not allow filtering the single events high space-time variability from the possible spatial heterogeneity).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, for orographic precipitation see also e.g. Harris et al (1996), Purdy et al (2001), Nykanen and Harris (2003) and Deidda et al (2006). Two main reasons were identified by Deidda et al (2006) as contributing to different outcomes in rainfall analyses: a physical factor lies in the different orographic range covered by the data (a limited range may not represent a significant obstacle for perturbations); a second explanation may be the differences in the length of the observation periods (relatively brief observation period may not allow filtering the single events high space-time variability from the possible spatial heterogeneity).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of storm event samples yield upper limits for the scaling range that are typically of the order of a few hours (even less than one hour), scales comparable to the mean storm duration (see e.g. Olsson et al, 1992;Onof et al, 1996;Harris et al, 1996;Purdy et al, 2001;Venugopal et al, 2006). Also the precipitation statistics are, in this case, for particular events.…”
Section: Distribution Of Rainfall Occurrences Characterized By Fractamentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reproduce observed spatial heterogeneity they multiplied a homogeneous spatial random cascade by a deterministic factor depending on the spatial location without linking it to local features. Analyzing a transect along the Southern Alps of New Zealand, Harris et al (1996) and Purdy et al (2001) found a dependence of scaling parameters on orography and rain features. More recently Deidda et al (2006) investigated the presence of rainfall spatial heterogeneity induced by orography on rainfall fields retrieved over Brazil by radars (TRMM-LBA, Tropical Rainfall Measurement Mission -Large Scale Biosphere Atmosphere Experiment).…”
Section: Introductionmentioning
confidence: 99%
“…The opportunity of introducing a heterogeneous component when modelling synthetic rainfall fields over land was investigated by Harris et al (1996), Jothityangkoon et al (2000), Purdy et al (2001), Pathirana and Herath (2002). Specifically Jothityangkoon et al (2000) and Pathirana and Herath (2002) analysed a 400 km×400 km area in southwestern Australia and a 128 km×128 km region centered in the Japanese archipelago, respectively.…”
Section: Introductionmentioning
confidence: 99%